Age-related changes in segmental accuracy and error production in Korean-English bilingual children: implications for clinical speech sound assessment procedures. (2nd January 2018) - Kim, Jae-Hyun; Ballard, Elaine; McCann, Clare
ABSTRACT: A lack of information about typical phonological development in bilingual children presents as a challenge to many speech-language pathologists assessing bilingual children with suspected speech sound disorder. This study investigated age-related changes in speech accuracy and error production in 16 preschool Korean-English bilingual children, aged between 3;1 and 5;11, in New Zealand. We found considerable individual variations in the longitudinal data. In particular, we found some error patterns emerged during the course of development, instead of being progressively resolved with age. Our findings suggest that speech-language pathologists should take a considered approach to identifying bilingual children with speech sound disorder solely based on the information provided in cross-sectional studies. We suggest that a follow-up session may provide valuable information facilitating the clinical assessment procedure to identify bilingual children with speech sound disorder.